PENINGKATAN PENYESUAIAN SOSIAL SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK - Ahmad Yanizon (JURNAL DIMENSI, 2013)
Low social adjustment of students who can hinder the development of adolescents, including social relationships with peers. Group counseling can be used to improve the social adjustment of students. This study aimed to reveal students' social adjustment through group counseling services. An experimental pretest and posttest control group design was used to test whether the guidance of a group can better improve the social adjustment of students. Two groups of students selected from a purposive sample of MAN 1 Curup and MAN 1 Kepahiang. Each group consisted of 10 students. Guidance for the experimental group performed in six sessions. Data the social adjustment of pretest-posttest gathered through. The findings of this study were: (1) there are significant differences between pre-test and post test experimental group on social adjustment. (2) there was no difference in pre-and post-test control group students on social adjustment. (3) there are significant differences in social adjustment between the experimental and control groups. Based on these findings, it can be concluded that students' social adjustment can be enhanced through the guidance of the group.